(untitled) (Journal Genta Kebidanan, 2024)
Primary dysmenorrhea is a normal process experienced during menstruation. Menstrual cramps are caused by very intense uterine muscle contractions, to release the uterine lining that is no longer needed. The impact of dysmenorrheal pain if it is not treated immediately will affect the mental and physical function of the individual so that it is urgent to take pharmacological or non-pharmacological action/therapy immediately. One of the non-pharmacological therapies that can be carried out is Spiritual Emotional Freedom Technique (SEFT) Therapy. Research Objective: To determine the effectiveness Spiritual Emotional Freedom Technique (SEFT) therapy on primary dysmenorrhea pain in young women at SMA Negeri 1 Tanjung Palas Tengah. Method: This research was a quasi experiment with a pretest posttest control group design, a population of 82 female students at SMA Negeri 1 Tanjung Palas Tengah, sampling using a purposive random sampling method of 21 female students. Inclusion of regular menstrual cycles 28-35 days, pain scale 1-6. Univariate test of frequency distribution and bivariate test, paired t-test, and independent t-test. Results: Dysmenorrhea pain decreased after the intervention of the SEFT group, paired T-test before the mean value was 4.67 after treatment 1.14, T-test p value 0.036 Ho was rejected SEFT was effective in reducing dysmenorrhea. Conclusion: Spiritual emotional freedom technique (SEFT) therapy reduces the intensity of primary dysmenorrhoea pain. SEFT therapy can be used as an alternative for treating dysmenorrhea pain